Analysis of Supplier Selection Based on Circular Economy in Fashion Retail Company Using the Fuzzy AHP Method - Banuwati, Ninis; Hasibuan, Sawarni (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2025)
Currently, the linear economic model applied in Indonesia still relies on a